The impact of family ownership on capital structure of firms: exploring the role of zero-leverage, size, location and the global financial crisis - Ramalho, J. J. S.; Rita, R. M. S.; da Silva, J. V. (International Small Business Journal, 2018)
In this article, we investigate the influence of family ownership on firm leverage across different subgroups of family and non-family firms. In addition, we examine the influence of firm size, geographical location and the 2008 global financial crisis on the capital structure of family firms. In both cases, we study the probability of firms using debt and, conditional on its use, the proportion of debt issued. We find that family ownership affects both decisions positively, namely, when the firm is large or located in a metropolitan area. For small firms located outside metropolitan areas, there is no clear family ownership effect. We also find the 2008 crisis had a substantial, but diversified, impact on family firm leverage. On the one hand, all family firms were more prone to use debt after 2008; on the other, the proportion of debt held by levered family firms decreased for micro and small firms, but increased for large firms. Overall, the crisis effects on family firm leverage seem to be the result of both supply- and demand-side factors, with the former particularly affecting the availability of debt to micro and small firms.